Intraoperative Cone Beam Tomography and Navigation for Displaced Acetabular Fractures: A Comparative Study. Issue 12 (December 2018) - Sebaaly, Amer; Jouffroy, Pomme; Emmanuel Moreau, Pierre; Rodaix, Camille; Riouallon, Guillaume
Abstract : Objectives: To evaluate the accuracy of reduction of the acetabular articular surface using an intraoperative computed tomography scanner (O-Arm) and screw navigation compared with a classical open technique. Design: Prospective matched cohort study. Setting: Tertiary referral center. Patients/Participants: Adult patients with acute acetabular fractures were included in the study. All patients were treated by 2 senior surgeons using intraoperative imaging and screw navigation. Main Outcome Measurements: The primary outcome measure was articular reduction. Secondary outcomes were radiation dosage, operative variables [operative time, time for image acquisition, intraoperative bleeding (cell saver), number of surgical plates, and number of screws], and postoperative variables (first postoperative day pain on the visual analog scale, postoperative transfusion, and hemoglobin change). P < 0.05 was considered statistically significant. Results: Thirty-five patients were treated in the inclusion period (2016–2017) and were matched to 35 cases in our database (2013–2016). Mean age was 43 years, and the most common fracture type was a both-column fracture (OTA/AO type C). Postoperative image analysis showed that reduction was achieved in 87.1% of the cases in the O-Arm group versus 64.7% in the control group ( P < 0.05). Mean gap of the articular fragments was 3.6 mm in the O-Arm group compared with 5.6 mm ( P = 0.01) in the control group. There was no significant difference between the 2 groups in regards to all other studied variables except a decrease in intraoperative blood loss and transfusions and an increase in surgical time with the O-Arm group. Finally, the total radiation dose was decreased using the intraoperative O-Arm compared with a routine postoperative computed tomography scan (dose length product in O-Arm: 498 mGy.cm; dose length product in historical group: 715 mGy.cm). Conclusions: Using intraoperative imaging and screw navigation for displaced acetabular fractures allow screw navigation with increasing articular surface reduction accuracy. Operative and anesthesia times were not increased, whereas radiation exposure to the patient was significantly decreased. We recommend the use of intraoperative imaging for the treatment of displaced acetabular fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.